The effect of commercial functional food with probiotics on microorganisms from early carious lesions (2020)
Objective: The aim of this study was to determine the effect of commercial functional food with probiotics on the growth of microorganisms from early carious lesions of children aged between six and 12. Materials and Methods: In this two-phase study, the first phase involved the selection and in vitro analysis of food from supermarkets. 100µl of food was inoculated in triplicate and at five different moments on solid BHI previously inoculated with Streptococcus mutans (S. mutans), and in BHI broth, to determine the inhibition of bacteria growth and pH of the medium, and the foods that gave the best results were selected. For the second phase, 100µl of the selected food was inoculated in triplicate at 3 different moments in solid and liquid BHI inoculated with microorganisms from children’s early carious lesions. The capacity for microorganisms growth inhibition and pH reduction was determined and compared using the Kruskall Wallis and Dunn tests. Results: Of the 23 foods identified, 14 were fermented milk products that generated a certain level of S. mutans growth inhibition. Of these, 4 were selected, including the one that showed the highest level of inhibition of the microorganisms growth from the carious lesions. Conclusion: The foods with probiotics have an inhibitive effect on microorganisms; however, it is important to consider that this is a measure that is complementary to those already used, as these probiotics also lower the medium’s pH. This study defines a candidate for a clinical study.